Design, Validation, and Economic Behavior of a Three-Phase Interleaved Step-Up DC–DC Converter for Electric Vehicle Application - Saravanakumar, T.; Saravana kumar, R. (Frontiers in Energy Research, 2022)
Due to the increasing number of direct current (DC) loads in electric vehicles (EVs), DC–DC converters are widely used in EV applications. Hence, a DC distribution system with DC–DC converters is more efficient. A three-phase interleaved step-up DC–DC converter (ISC) has been proposed for use in electric vehicles. Other uses of the proposed ISC converter include aircraft, satellites, industrial, and traction drives. The proposed converter is subjected to a thorough frequency response study, which is explained in detail. The design technique recommends the proper quantity of switches to be used in the system. The reduction in the number of switches results in a 94% increase in the efficiency of this converter. The economic aspects of ISC, such as cost analysis and its procedure, have been discussed. Design models were checked using MATLAB/Simulink, which was interfaced with the real-time simulator OPAL-RT (OP5700) to ensure that they were appropriate. The results have been presented in detail.